Hubungan Pengetahuan Ibu Post Partum tentang Manfaat Kolostrum dengan Pemberian Kolostrum pada Bayi Baru Lahir - Kustini Kustini (Universitas STRADA Indonesia, 2018)
The knowledge of post partum mothers about the benefits of colostrum is very important. Colostrum is the best nutrition for babies because the composition of nutrients in it is optimally able to guarantee the growth of the baby's body. The quality of nutrients is also best because it is easily absorbed and digested by the baby's intestines. The results of the initial survey found that most post partum mothers did not give colostrum. The purpose of this study was to determine the relationship of knowledge of post partum mothers about the benefits of colostrum with the administration of colostrum in newborns at the Polindes of Karangwedoro Village, Turi District, Lamongan Regency in May-June 2018. This type of research is analytic with cross sectional approach. The number of population in this study is the population of post partum mothers as many as 30 post partum mothers